Antibiotics : Actions, Origins, Resistance - Walsh, Christopher (ASM Press, 2003)
As antibiotics become deactivated through resistance and emerging bacterial diseases Christopher Walsh offers new insights into antibiotic modification and design. He shows how antibiotics work on targets and reviews recent strategies for finding innovative antibiotics to replace the last generation.